2009
DOI: 10.1177/175114370901000220
|View full text |Cite
|
Sign up to set email alerts
|

Management of Inhalational Injuries in UK Burns Centres – a Questionnaire Survey

Abstract: Management of inhalational burn injuries in UK specialist centres varies widely, according to this survey, which was carried out in 2008. Areas investigated included the use, or not, of therapeutic bronchoscopy, the use of nebulised agents, ventilatory support strategies and pharmacological treatments used to decrease the incidence of pneumonia. Evidence-based guidelines do not currently exist. The survey has led to setting up a National Consensus Working Group to develop nationally agreed guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The present study highlights the challenges in burn care with the paucity of evidence. The only other nationwide survey investigating the management of INHI was conducted by Prior et al (25) in the United Kingdom. The authors reported that 81% of the burn units in the United Kingdom require fibreoptic bronchoscopy to diagnose INHI, and no unit uses a purely clinical diagnosis; 76% of the units use nebulizing medications in treating INHI.…”
Section: Figure 2) Physical Examination Findings Guiding Intubation Fmentioning
confidence: 99%
“…The present study highlights the challenges in burn care with the paucity of evidence. The only other nationwide survey investigating the management of INHI was conducted by Prior et al (25) in the United Kingdom. The authors reported that 81% of the burn units in the United Kingdom require fibreoptic bronchoscopy to diagnose INHI, and no unit uses a purely clinical diagnosis; 76% of the units use nebulizing medications in treating INHI.…”
Section: Figure 2) Physical Examination Findings Guiding Intubation Fmentioning
confidence: 99%